Advances in Practical Multi-Agent Systems - Bai, Quan.; Fukuta, Naoki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Multi-Agent System (MAS) is an exciting, emerging paradigm expected to play a key role in many society-changing practices. The International Conference on Principles and Practice of Multi-Agent Systems (PRIMA) is a leading scientific conference for research on intelligent agent systems and multi-agent systems, attracting high quality, state-of-the-art research from all over the world. PRIMA$1 (B09 was the 12th in the series of PRIMA conferences and was held in Nagoya, Japan. Beside a single-track main conference, PRIMA$1 (B09 also included a number of workshops which were designed to provide a forum for researchers and practitioners to present and exchange the latest developments at the MAS frontier. This book constitutes the post-proceedings of workshops under PRIMA$1 (B09. Readers will be able to explore a diverse range of topics and detailed discussions related to a number of important themes in our ever changing world. This collection plays an important role in bridging the gap between MAS theory and practice. It emphasizes the importance of MAS in the research and development of smart power grid systems, decision support systems, optimization and analysis systems for road traffic and markets, environmental monitoring and simulation, and in many other real-world applications and publicizes and extends MAS technology to many domains in this fast moving information age.s
Part I Agent-based Collaboration, Coordination and Decision Support -- Part II Agent-based Simulation for Complex Systems: Application to Economics, Finance and Social Sciences -- Part III Agent Technology for Environmental Monitoring and Disaster Management.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).